NAVIGATING ADOLESCENCE: UNDERSTANDING HEDONISTIC LIFESTYLES AMONG INDONESIAN TEENAGERS - Ferdiansyah; Afriana, Renny; Surtiyoni, Endang (CV. TOTUS TUUS, 2024)
During adolescence, teenagers are often influenced by various factors that shape their lifestyle choices. This study investigates the hedonistic lifestyle among